New Age and neopagan religions in America - Pike, Sarah M. (Columbia contemporary American religion series, 2004)
Provides a general introduction to the varieties of New Age and Neopagan religions in the United States today as well as an account of their nineteenth-century roots and emergence from the 1960s counterculture. Covering such topics as healing, gender and sexuality, millennialism, and ritual experience, it also provides a description and analysis of the spiritual worlds and social networks created by participants